Lactic Acid Bacteria Isolated From Korean Kimchi Activate the Vitamin D Receptor–autophagy Signaling Pathways. Issue 8 (14th March 2020) - Lu, Rong; Shang, Mei; Zhang, Yong-Guo; Jiao, Yang; Xia, Yinglin; Garrett, Shari; Bakke, Danika; Bäuerl, Christine; Martinez, Gaspar Perez; Kim, Cheol-Hyun; Kang, Sang-Moo; Sun, Jun
Abstract: Background: Probiotic lactic acid bacteria (LAB) have been used in the anti-inflammation and anti-infection process of various diseases, including inflammatory bowel disease (IBD). Vitamin D receptor ( VDR ) plays an essential role in pathogenesis of IBD and infectious diseases. Previous studies have demonstrated that the human VDR gene is a key host factor to shape gut microbiome. Furthermore, intestinal epithelial VDR conditional knockout (VDR ΔIEC ) leads to dysbiosis. Low expressions of VDR is associated with impaired autophagy, accompanied by a reduction of ATG16L1 and LC3B. The purpose of this study is to investigate probiotic effects and mechanism in modulating the VDR -autophagy pathways. Methods: Five LAB strains were isolated from Korean kimchi. Conditional medium (CM) from these strains was used to treat a human cell line HCT116 or intestinal organoids to measure the expression of VDR and autophagy. Mouse embryonic fibroblast (MEF) cells with or without VDR were used to investigate the dependence on the VDR signaling. To test the role of LAB in anti-inflammation, VDR +/+ organoids were treated with 121-CM before infection with Salmonella enterica serovar Enteritidis. In vivo, the role of LAB in regulating VDR -autophagy signaling was examined using LAB 121-CM orally administrated to VDR Loxp and VDR ΔIEC mice. Results: The LAB-CM-treated groups showed higher mRNA expression of VDR and its target genes cathelicidin compared with the control group. LAB treatment also enhanced expressions of Beclin-1 and ATG16L1 and changed the ratio of LC3B I and II, indicating the activation of autophagic responses. Furthermore, 121-CM treatment before Salmonella enterica serovar Enteritidis infection dramatically increased VDR and ATG16L1 and inhibited the inflammation. Administration of 121-CM to VDR Loxp and VDR ΔIEC mice for 12 and 24 hours resulted in an increase of VDR and LC3B II:I ratio. Furthermore, we identified that probiotic proteins P40 and P75 in the LAB-CM contributed to the anti-inflammatory function by increasing VDR . Conclusions: Probiotic LAB exert anti-inflammation activity and induces autophagy. These effects depend on the VDR expression. Our data highlight the beneficial effects of these 5 LAB strains isolated from food in anti-infection and anti-inflammation. Abstract : Lactic acid bacteria from Korean kimchi increase vitamin D receptor and autophagy signaling. Proteins P40 and P75 in lactic acid bacteria contributed to the anti-inflammatory function by increasing VDR . This study indicates the beneficial effects of probiotics in anti-infection and anti-inflammation.